Neurocinema-the sequel : a history of neurology on screen - Wijdicks, Eelco F. M.; Wijdicks, Eelco F. M.
"The history of neurology as seen through the lens of the filmmaker is fascinating and extraordinary. Neurocinema, The Sequel is a review of the history of neurology as seen in film, starting with the early days of cinema and concluding with contemporary films now available in theaters and on streaming sites. The major themes of this book encompass how neurology has been represented in the history of cinema and how neurologic topics emerged and then disappeared, with some staging a comeback in more recent films. 180 films are assessed and rated, and many of these are exemplary depictions of neurological disorders. The author examines whether film, from a neurologic perspective, can provide insight and even debate. Each of the films discussed in this book demands serious attention by those who see and manage neurologic patients and support their families. Neurocinema, The Sequel chronicles this archive of neurologic representation, drawing readers in a rich collection of cinematic wonders of permanent cultural and historical value"--
INTRODUCING THE HISTORY OF MEDICINE IN FILM -- INTRODUCING THE HISTORY OF NEUROLOGY IN FILM -- THE NEUROLOGIST IN FILM -- THE NEUROLOGIC DISORDERS IN FILM -- NEUROETHICS IN FILM -- NEUROLOGY IN DOCUMENTARIES -- NEUROCELEBRITIES IN FILM -- NEUROFOLLIES IN FILM -- COME AND SEE : WHAT TO GET OUT OF NEUROCINEMA.
Sequel to Neurocinema : when film meets neurology / Eelco F.M. Wijdicks. 2015.
Includes bibliographical references and index.
Keywords: Medicine in the Arts; Motion Pictures; Neurology; Nervous System Diseases; Neurologists; History, 20th Century; History, 21st Century